2018
DOI: 10.1016/j.ebiom.2018.10.055
|View full text |Cite
|
Sign up to set email alerts
|

An acellular bioresorbable ultra-purified alginate gel promotes intervertebral disc repair: A preclinical proof-of-concept study

Abstract: BackgroundThe current surgical procedure of choice for lumbar intervertebral disc (IVD) herniation is discectomy. However, defects within IVD produced upon discectomy may impair tissue healing and predispose patients to subsequent IVD degeneration. This study aimed to investigate whether the use of an acellular bioresorbable ultra-purified alginate (UPAL) gel implantation system is safe and effective as a reparative therapeutic strategy after lumbar discectomy.MethodsHuman IVD cells were cultured in a three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(184 citation statements)
references
References 62 publications
(132 reference statements)
6
178
0
Order By: Relevance
“…Thus, it might be free from potential animal pathogens. Furthermore, in vivo biological safety tests based on an international organization for standardization (ISO) and good laboratory practice standards showed that UPAL does not have immunogenicity to the human body 31 . In addition, the UPAL group provided more CD31-and HNF4α-positive cells than any other groups, illustrating that UPAL coating not only increased the engraftment area but also increased the expression of vascular endothelial cells and hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it might be free from potential animal pathogens. Furthermore, in vivo biological safety tests based on an international organization for standardization (ISO) and good laboratory practice standards showed that UPAL does not have immunogenicity to the human body 31 . In addition, the UPAL group provided more CD31-and HNF4α-positive cells than any other groups, illustrating that UPAL coating not only increased the engraftment area but also increased the expression of vascular endothelial cells and hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other coating agents, UPAL yielded the best effect in improving transplant tissue survival rate and replenishing the liver function. Moreover, the intradiscal injection of UPAL gel can suppress lumbar intervertebral disc degeneration and promote the production of extracellular matrix, essential for nucleus pulposus cell function after discectomy 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The Pfirrmann grading score was used for quantitative analysis of degenerative changes in rabbit lumbar IVDs. Alterations in NP were quantified using relative MRI index, as described previously . No significant difference was detected in the Pfirrmann grading score and relative MRI index among all groups at 6 or 12 months (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Quantitative analysis of T2‐weighted, mid‐sagittal image slices was also processed using the Analyze 10.0 software (AnalyzeDirect, Overland Park, KS), as reported previously . The MRI index (product of NP area and average signal intensity) was used for the quantification of alterations in NP, and quantitative data were expressed as percentage relative to the MRI index obtained with untreated control disks (relative MRI index) . All image assessments were performed by two independent blind observers, and the quantitative data were presented as the mean of the three evaluations ( n = 8 disks for each treatment group/time point) …”
Section: Methodsmentioning
confidence: 99%
“…Alginate gels have been extensively studied for tissue engineering applications as cell encapsulation material as well as for in vivo cell delivery as an injectable 3D matrix. Several studies demonstrated that calcium alginate gel, although easy to obtain, exhibited poor biodegradation, bioresorbability and cell adhesion [ 112 ]. For example, ultrapurified alginate gels are biocompatible with human lumbar intervertebral disc cells and promote extracellular matrix production after discectomy.…”
Section: Applications Of Alginate In the Medical Fieldmentioning
confidence: 99%